Biomaterials, organic and intelligent materials : proceedings of the Symposia N: biomaterials, O: catalytic materials, Q: ordered polymers, R: photo- and electro-responsive materials, T: biosensors, EE: construction and functions of organic thin films, FF: intelligent materials of the 3rd IUMRS International Conference on Advanced Materials, Sunshine City, Ikebukura, Tokyo, Japan, August 31 - September 4, 1993 - Aoki, Hideki (Transactions of the Materials Research Society of Japan ;, 1994)
Advanced Materials '93.